Efficacy of Potassium Aluminum Sulfate (KALSO4)2 and Povidone Iodine (C6H9I2NO) as Crede’s Prophylaxis against Ophthalmia Neonatorum - Mendoza, Leonel (JPAIR Multidisciplinary Research, 2018)
Neonatal conjunctivitis is a worldwide problem. Although global incidence is not known, incidents of 1-24% have been reported from various regions of the world especially those practicing home delivery without standard prophylaxis. This study was an in-vitro investigation on possible prophylaxis for ophthalmia neonatorum (ON) like potassium aluminum sulfate (KAlSO4)2 and povidone iodine (C6H9I2NO) in comparison to tetracycline. A five by three (5x3) factorial experiment in Completely Randomized Design (CRD) was used in this study. Factor A was the five-test bacteria, namely Staphylococcus aureus, Escherichia coli, Klebsiella pneumoniae, Enterobacter spp. and Pseudomonas spp. while Factor B was the experimental variables or the substances to be tested such as alum, povidone iodine and tetracycline. Aluminum was diluted and subjected to purity test prior to bacteria assay. The zone of inhibition was measured using a caliper and results were recorded. Based on the in-vitro analysis, aluminum showed a positive response to the five tested bacteria as it yielded a comparative mean results of growth inhibition. Among the possible applications of the findings in the study could be the formulation of antiseptic eye drops with the use of alum or Povidone iodine to be used as prophylaxis to guard against neonatal conjunctivitis.